The impact of foreign direct investment on economic growth:the Portuguese experience - Leitão, Nuno Carlos (2013)
This study examines the link between economic growth and foreign direct investment for Portugal. Using a panel data approach, the results show that there is convergence among Portugal and her trading partners. Our results also demonstrate that foreign direct investment and bilateral trade promote economic growth. The growth is negatively correlated with inflation and the initial level of GDP per capita. As in previous studies taxes plays a minor role on determining the growth.